2009
DOI: 10.1021/jf902315e
|View full text |Cite
|
Sign up to set email alerts
|

6-Shogaol, an Active Constituent of Dietary Ginger, Induces Autophagy by Inhibiting the AKT/mTOR Pathway in Human Non-Small Cell Lung Cancer A549 Cells

Abstract: This study is the first study to investigate the anticancer effect of 6-shogaol in human non-small cell lung cancer A549 cells. 6-Shogaol inhibited cell proliferation by inducing autophagic cell death, but not, predominantly, apoptosis. Pretreatment of cells with 3-methyladenine (3-MA), an autophagy inhibitor, suppressed 6-shogaol mediated antiproliferation activity, suggesting that induction of autophagy by 6-shogaol is conducive to cell death. We also found that 6-shogaol inhibited survival signaling through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(104 citation statements)
references
References 29 publications
3
101
0
Order By: Relevance
“…Previously published studies have shown the potential antiproliferative and apoptosis inducing activity of 6-SHO in lung, colorectal, liver and, hematologic cancer cells (15,(30)(31)(32). In the present study, 6-SHO was also shown to be effective at inhibiting the growth of HMVP2 cells in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…Previously published studies have shown the potential antiproliferative and apoptosis inducing activity of 6-SHO in lung, colorectal, liver and, hematologic cancer cells (15,(30)(31)(32). In the present study, 6-SHO was also shown to be effective at inhibiting the growth of HMVP2 cells in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…5,6 Correspondingly, a recent study has shown that inhibition of PI3K/AKT/ mTOR signaling is consistently associated with suppressed proliferation by cancer cells. 54 Similarly, Lee at al have reported that a traditional herbal medicine, Andrographis paniculate, contributes to an inhibition of migration and invasion by NSCLC via downregulation of the PI3K/Akt signaling pathway. 39 On the other hand, several apoptosis markers were examined, including Bax, caspase 3, and PARP, and the SQE treatment had no observable effect on cell death/apoptosis in our experimental conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Rapamycin induces apoptosis only in cells lacking functional p53, and Huang et al have shown that their results may be useful in the conceptual development of tumor-selective therapy with rapamycin analogs or other inhibitors of mTOR (27). However, some studies show that mTOR inhibitors induce cell death in some malignancies by autophagy rather than apoptosis (10,28). Recent studies also indicate that inhibition of the Akt/mTOR pathway is consistently associated with triggering autophagy in cancer cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTOR affects pathway-mediated transcription and translation, leading to cell cycle arrest and anti-angiogenesis. Regarding the anti-tumor mechanism of mTOR inhibitors, some studies indicate that inhibitors of Akt and its downstream target, mTOR signaling, have anti-tumor effects because inhibition of this pathway contributes to the initiation of autophagy (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%